1978
DOI: 10.1073/pnas.75.9.4165
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic factors and form determination of the head of bacteriophage T4.

Abstract: The form of the bacteriophage T4 prehead is described by its icosahedral symmetry, its diameter, and its length. We show how each oftheseparameters is regulated during prehead formation and ascribe specific form-determining functions to the prehead proteins. The major protein of the head shell can assemble in several different forms. The structure produced in vivo depends on the rate of synthesis of the major protein relative to the rates of synthesis of minor shell proteins and the major core protein. From ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…Serwer and Hayes also suggested that the T7 phage head carries an overall negative charge and that tail fibers are positively charged (35). The pK a values for major T4 head proteins ranged from 4.62 to 6.63, while that of the tail sheath was 4.80, with a range between 5.21 and 9.76 being reported for tail fiber proteins (5,17,36). These earlier data and the results of this study support our conclusion that phage heads exert a net negative charge, which can interact electrostatically with positively charged surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Serwer and Hayes also suggested that the T7 phage head carries an overall negative charge and that tail fibers are positively charged (35). The pK a values for major T4 head proteins ranged from 4.62 to 6.63, while that of the tail sheath was 4.80, with a range between 5.21 and 9.76 being reported for tail fiber proteins (5,17,36). These earlier data and the results of this study support our conclusion that phage heads exert a net negative charge, which can interact electrostatically with positively charged surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of portal assembly into a polyhedral capsid has been studied for many years in dsDNA bacteriophages, such as T4, 29, P22, and SPP1 (2,7,8,9,25,33). As in the case of HSV-1, bacteriophage portals are (i) cone-shaped structures formed from 12 or 13 copies of a single polypeptide, the portal protein; (ii) located at a unique vertex of the capsid polyhedron, where they serve as a channel for DNA to enter and exit; and (iii) a Capsids were assembled in vitro as described in Materials and Methods in the presence or absence of added portals.…”
Section: Discussionmentioning
confidence: 99%
“…The prohead is loosely assembled with a precursor form of gene product gp21. gp2l is activated by autodigestion and is the proteinase responsible for cleavage of at least six other prohead proteins (318)(319)(320)(321). Concurrent with cleavage, DNA is packaged and the ultimate product, a stable packaged head structure, is formed.…”
Section: Vilral Proteinasesmentioning
confidence: 99%